Is it Possible to be a Revolutionary and Like Flowers? : A Contemporary Floriography. - Burgering, Eva; ten Cate, Heske; Sam, Eleonoor Jap; van de Walle, Robert; Cluitmans, Laurie; Zeqo, Arnisa (Den Haag : Nest, 2021)
Atashi, Mehraneh ; Biscotti, Rossella ; Bonilla, Milena ; CPR ; Geene, Anne ; Gufler, Philipp ; Gluklya ; Henrot, Camille ; Kaersenhout, Patricia ; Nkanga, Otobong ; Noorda, Ruchama ; Pask, Maria ; van der Stokker, Lily
Is it possible to be a revolutionary and like flowers? Een hedendaagse floriografie, Een tentoonstelling bij Nest/An exhibition at Nest, Den Haag, 10.9. - 19.12.2021
boek